Methodologies for Seismic Soil-Structure Interaction Analysis in the Design and Assessment of Nuclear Installations - IAEA (IAEA-TECDOC., 2022)
Presents soil-structure interaction (SSI) phenomena and current practices in SSI modelling, simulation methodology and analysis methods for the design and assessment of nuclear installations.